La población juvenil y su participación como fuerza de trabajo y su incidencia en la economía del cantón Quevedo año 2013 - Roque Macías, Sabina Paola (2015)
Research on the impact of the youth population as a labor force in the economy of the canton Quevedo has the general purpose worry about the possibility of integrating into working life to the people who for various reasons are unemployed, although they are able to you perform in any type of employment, this objective is considered that the proposed study will present alternatives and appropriate for the possibility of inserting the workforce to youths 18 to 29 years of age by some reason are unemployed strategies and the achieving the objective will impact positively on the economy of the canton, improving their socio-economic situation and therefore his family. The Study contains an analysis of current issues related to young people, through the statement of the problem, performing a diagnostic that allowed the problem to develop and systematize the formulation of objectives, assumptions and justification arises the theoretical framework with the most relevant information obtained through secondary sources of information, methods, techniques, types and sources of information are identified, to then find the results according to the objectives that can reach the respective conclusions and recommendations.